Efeito do agonista (G-1) do receptor de estrogênio acoplado a proteína G (GPER) sobre a reatividade vascular mesentérica de ratos espontaneamente hipertensos de ambos os sexos - Delgado, Nathalie Tristão Banhos (2021)
Introduction: The protective effect of oestrogen on the cardiovascular system (CVS) cannot be explained only by its actions through ERα and ERβ receptors. Gprotein-coupled oestrogen receptors (GPER) may also be involved in this response. Therefore, in this study, we evaluated the GPER-mediated vascular response using a specific agonist, G-1, in spontaneously hypertensive rats (SHR). Our hypothesis is that G-1 induces a relaxation response in SHR resistance mesenteric arteries of both sexes. Methods: Concentration-response curves with G-1 (1 nM-10 μM) were performed in SHR mesenteric arteries of both sexes (10 – 12 weeks) before and after endothelial removal or incubations with nitric oxide synthase inhibitor (L-NAME 300 µM), cyclooxygenase inhibitor (Indomethacin, INDO - 10 µM), isolated or combined with a nonspecific cytochrome P450 inhibitor (Clotrimazol, CLOT - 0.75 µM) or a hydrogen peroxide (H2O2) degrader (Catalase, CAT - 1000 units / mL). We also evaluated the effect of Tiron, an O2 ●- scavenging, and a non-selective blocking of K+ channels (Tetraethylammonium, TEA - 5 mM). Immunofluorescence techniques were used for GPER, H2O2, and reactive oxygen species (ROS). Concentration curve for acetylcholine (ACh, 0.1 nM - 10 µM) and phenylephrine (PE, 1 nM - 100 µM) were also evaluated after incubations with 0.1 and 10 µM of G-1. We evaluated weight and hemodynamic parameters, as well as reactivity to bradykinin (BK, 0.1 nM - 10 µM) and PE (1 nM - 100 µM) after treatment for 15 days with G36, a selective GPER antagonist (160 μg/Kg/ day) in SHR females. Results: GPER activation promoted a similar relaxation response between SHR males and females. In males, relaxation depends on vascular smooth muscle, NO, and H2O2 pathway, while in females, on the endothelium and H2O2. The fluorescence intensity for GPER was higher in females and G-1 was able to stimulate the production of only H2O2 in both sexes. The presence of 0.1 µM G-1 improved the ACh-induced relaxation response and reduced the PE-induced vasoconstrictor response only in females. Treatment with G36 did not change weight, hemodynamic and vascular reactivity parameters. Conclusion: GPER activation induces a relaxation response in the mesenteric arteries of SHR rats of both sexes with the participation of different endothelial mediators and modulates vasodilator and vasoconstrictor agonist responses. These results contribute to improve the understanding of GPER actions on vascular reactivity within essential hypertension.